Between the east and the west: islam and the post colonial arabic novels in Libya (2015)
This paper explores how Islam appears and as viewed by the public in post colonial Libyan novels. It answers the controversial question regarding the shocking and dramatic change in ideology among Libyan intellectuals, especially the novelists, who switch to western ideologies at a certain stage in their lives. Although, critics have touched the similarity between Islam and Western ideology, but no one has investigated the Arabic novels of Libya that problematise this transformation, leading to a better understanding of this genre of literary creativity. Its emphasis on Islam in post colonial Libyan novels is not intended to minimise the role of non-literary writings by Libyan Arab and non- Libyan writers since the mid-nineteenth century. However, it is the contention of this paper that Islam in post colonial Libyan novels in the post colonial period goes beyond the limit of specific discipline. It is better equipped to provide us with multiple perspectives and concrete situations, which are very important to answer questions that are continually raised by scholars regarding the so-called issues on Islam and Libya post colonial novels.